The Image of the Jews in the Travel Book Orient by Vicente Blasco Ibáñez - Mirjana M. Sekulić (Etnoantropološki Problemi, 2022)
In this article we study the image of the Jewish people in Vicente Blasco Ibáñez's travel book Orient. The book describes the author’s journey from France to the Orient, more specifically Istanbul, in 1907. The first descriptions of the Jews already appear in the first text of the book, in which the author depicts the small spa town of Vichy in France. The author describes different nationalities gathered in Vichy, remarking on its cosmopolitan atmosphere. In Vichy, he identifies a few Jewish nationals as paradigmatic characters - stereotyped visions of beautiful cocotte or good Rebecca/Miriam in the company of her husband, who is marked by greed and stinginess as racial characteristics, thus expressing his prejudiced views towards the Jews.  Later on, on his journey to the East, Blasco Ibáñez spends two days in Serbia, leaving a testimony about the Serbian people, but also about an encounter with some Sephardic Jews in Belgrade. A similar meeting will take place in Istanbul, prompting the author to express his wish to continue writing about this nation in the future. In the travel book Orient, Blasko Ibáñez presents the Sephardim and discusses their language and nostalgic need to reconnect with Spain. Through the author’s presentation and selection of Sephardic attributes we can draw some conclusions about his personal attitude that preserves some Judeophobic elements